Social currency: Influencer marketing’s role in shaping digital strategies - Jacob, Sanjana Chinnu; Edwin, T S (The International tax journal, 2026)
In the ever-changing realm of digital marketing, influencer marketing has emerged as a crucial catalyst, reshaping strategies and exerting influence on consumer behavior. This study delves into the pivotal role played by influencer marketing, exploring its profound impact on shaping digital strategies. The primary aim is to elucidate how influencers employ "social currency," utilizing their online presence and connection with audiences to shape brand perception and influence purchasing decisions. The methodology employed entails a comprehensive examination of contemporary literature, empirical case studies, and industry insights to illuminate the intricate dynamics between influencers and the digital marketing ecosystem. By scrutinizing various successful campaigns and strategies, this article aims to underscore the strategic significance of influencer marketing in transforming brand engagement, fostering customer loyalty, and expanding market reach within the digital domain. Specifically, this research will analyze the mechanisms through which influencers utilize social media platforms to captivate audiences and enhance brand awareness. Additionally, it will dissect the collaborative relationship between brands and influencers, investigating the subtleties of content creation, audience targeting, and performance measurement strategies employed in successful influencer campaigns.